HUBUNGAN KECERDASAN SPIRITUAL TERHADAP STRES PADA REMAJA - Rosma, Febriana; D Mustamu Qomal Pa’ni; Aoladul Muqarrabin; Teguh Achmalona; Baiq Fitrihan Rukmana (Journal Of Nursing Science Research, 2024)
The research aims to determine the effect of spiritual intelligence on stress in teenagers at the Nurul Hidayah prayer room. This research uses a quantitative approach with a non- experimental design. The research population was all teenagers at the Nurul Hidayah prayer room and a sample of 24 people were taken using the Slovin formula with simple random sampling technique. The data collection method used the SWBS and DASS-21 questionnaires. Data analysis used chi-square analysis. The results of this research show that there is an influence of spiritual intelligence on stress with evidence of ? value = 0.009 < ? = 0.05, so that there is a significant influence of spiritual intelligence on stress levels in Nurul Hidayah prayer room teenagers. The higher a teenager's spiritual intelligence, the lower a person's stress level.